INFLUENCE OF ENRICHED BIO-DIGESTER LIQUID MANURE ON GROWTH AND YIELD OF FINGER MILLET - SAUNSHI, SUDHEENDRA; V. C. REDDY,; MALLIKARJUN,; RAWAL, RAJESH (The Bioscan, 2014)
Application of enriched bio-digester liquid manure (BDLM) with poultry manure & rock phosphate equivalent to 60 kg N ha-1 had led lead to the significant grain yield (3893 kg ha-1) and straw yield (7228 kg ha -1) of finger millet compared to recommended practice which was in turn due to growth parameters viz., plant height, leaf area index, dry matter production and tillers.